2002
DOI: 10.1128/iai.70.12.6638-6645.2002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Expression of Toll-Like Receptors and Their Reactivities in Dendritic Cells in BALB/c and C57BL/6 Mice

Abstract: We have previously reported that differences in early production of interleukin 12 (IL-12) by dendritic cells (DC) underlies the difference between the susceptibilities to Listeria monocytogenes of C57BL/6 and BALB/c mice. To elucidate mechanisms for the different abilities of DC to produce cytokine in C57BL/6 and BALB/c mice, we examined Toll-like receptor (TLR) expression by DC and their responses in vitro to known microbial ligands for TLRs. We found that DC isolated from the spleens of naive C57BL/6 mice p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
88
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(100 citation statements)
references
References 49 publications
9
88
0
3
Order By: Relevance
“…We excluded the possibility that the differential regulation of the cytokine transcription in the two strains by CpG-ODN was also affected indirectly by differences in TLR9 levels and/or signal transduction events mediated by this receptor. It is of note that different results were obtained when dendritic cells from these strains were studied (48). In this work, a higher expression of TLR9 was demonstrated in C57BL/6, and no significant difference in TNF-␣ release in response to CpG-ODN was found.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…We excluded the possibility that the differential regulation of the cytokine transcription in the two strains by CpG-ODN was also affected indirectly by differences in TLR9 levels and/or signal transduction events mediated by this receptor. It is of note that different results were obtained when dendritic cells from these strains were studied (48). In this work, a higher expression of TLR9 was demonstrated in C57BL/6, and no significant difference in TNF-␣ release in response to CpG-ODN was found.…”
Section: Discussionmentioning
confidence: 58%
“…B, cells were treated with CpG-ODN for 60 min (lanes 2-11; untreated control, lane 1), nuclear extracts were prepared from BALB/c-and C57BL/6-derived cells (upper and lower panels, respectively), and the ability of B2a derived from either BALB/c (lanes 3-5) or C57BL/c (lanes 6 -8) as well as unlabeled B consensus sequence (lanes 9 -11) to compete with the B consensus sequence was measured using electrophoretic mobility shift assay. (48) was measured in medium collected after 24 h of incubation with CpG-ODN, while we measured TNF-␣ after 4 and 6 h. CpG-ODN also impacts the cytokine via message stabilization but to a similar degree in the two mice, consistent with 100% homology at the AU-rich elements known to play a role in the message stability (21,31). It has been shown that the mitogen-activated protein kinase p38 cascade is involved in regulating mRNA stability via 3Ј-untranslated regions of several mRNAs including TNF-␣ mRNA (49).…”
Section: Discussionmentioning
confidence: 99%
“…6). Activated/Matured endogenous mouse DCs are characterized by high surface expression of costimulatory molecules such as CD40, CD80, and CD86 (48). In this study, we choose to show expression of CD86 as an example to postulate that HP-NAP-induced migrating DCs have an activated/matured phenotype (49).…”
Section: Discussionmentioning
confidence: 99%
“…In addition and despite that no functional consequences have been observed upon zymosan recognition, nonsynonymous single nucleotide polymorphisms have been identified in C57BL/6 mice by genetic comparison with the BALB/c background, 21 suggesting additional functional variability of dectin-1 between these strains. In this regard, as cooperative signaling between dectin-1 and other PRRs is crucial for efficient recognition of C. albicans cells, 10 the differences in TLR2 and mannose receptor expression observed among different inbred strains of mice 29,30 may offer an additional plausible explanation.…”
Section: Discussionmentioning
confidence: 99%